RATIONAL AND IRRATIONAL ASPECTS OF FORMATION ON THE BASIS OF DECONSTRUCTIVISM IN THE FASHION INDUSTRY - Гасем, Аміна Мерзаківна (Art and Design, 2024)
Objective: to study the manifestations of deconstruction in fashion design in a rational and irrational sense; to analyze the practical application of these manifestations in fashion design and their direct impact on the formative process in costume design; to justify the use of deconstruction methods as a new tool in creating new forms and images in design practices. A systematic approach and such research methods as artistic, figurative and stylistic analysis, visual and analytical approach, abstraction method, comparative method and systematisation of the results obtained were applied. The analysis of modern forms of clothing developed on the basis of deconstructivism has made it possible to establish which features of deconstructivism designers mainly use in the formation of modern costumes, in particular: emphasis on individual elements of the costume; use of the principle of asymmetry; hyperbole as a deliberate exaggeration of the scale of individual elements or the product as a whole; creation of dynamic, contrasting compositions; departure from the classical rules of design; movement, use of non-standard materials, etc. In fact, this is the basis for the use of rational and irrational approaches to the creation of modern clothing. The article illustrates the characteristic means of applying rational and irrational deconstruction techniques. The peculiarities of the manifestations of the rational and irrational in the shaping of clothing in the modern fashion industry are analysed. Scientific novelty of the results obtained is to determine the systematisation and classification of the main rational and irrational features of deconstruction, their practical application in fashion design. The specifics of their interpretations in contemporary fashion are analysed. The importance of the conceptual component in rational and irrational approaches is emphasised. The results of the study can contribute to a deeper study of deconstruction as a method of shaping in contemporary design. The materials of the article are intended for use in the educational process in the training of fashion designers and stylists. They can also be used in writing scientific papers on the relevant topics. The results of the study can be useful for the development of modern clothing collections, in the author's direct design activity.